Integrated Analysis of Engineered Carbon Limitation in a Quadruple CO2/HCO3 − Uptake Mutant of Synechocystis sp. PCC 6803 . Issue 3 (15th September 2015) - Orf, Isabel; Klähn, Stephan; Schwarz, Doreen; Frank, Marcus; Hess, Wolfgang R.; Hagemann, Martin; Kopka, Joachim
Abstract : Engineered carbon limitation after deletion of four Ci-uptake systems in Synechocystis sp. PCC 6803 is compensated by an extensive phenocopy of wild-type acclimation to low CO2 and multilayered Ci regulation. Abstract: Cyanobacteria have efficient carbon concentration mechanisms and suppress photorespiration in response to inorganic carbon (Ci ) limitation. We studied intracellular Ci limitation in the slow-growing CO2 /HCO3 − -uptake mutant Ɗ ndhD3 (for NADH dehydrogenase subunit D3)/ndhD4 (for NADH dehydrogenase subunit D4)/cmpA (for bicarbonate transport system substrate-binding protein A)/sbtA (for sodium-dependent bicarbonate transporter A ): Ɗ 4 mutant of Synechocystis sp. PCC 6803. When cultivated under high-CO2 conditions, ∆4 phenocopies wild-type metabolic and transcriptomic acclimation responses after the shift from high to low CO2 supply. The ∆4 phenocopy reveals multiple compensation mechanisms and differs from the preacclimation of the transcriptional Ci regulator mutant ∆ndhR (for ndhF3 operon transcriptional regulator ). Contrary to the carboxysomeless ∆ccmM (for carbon dioxide concentrating mechanism protein M ) mutant, the metabolic photorespiratory burst triggered by shifting to low CO2 is not enhanced in ∆4 . However, levels of the photorespiratory intermediates 2-phosphoglycolate and glycine are increased under high CO2 . The number of carboxysomes is increased in ∆4 under high-CO2 conditions and appears to be the major contributing factor for the avoidance of photorespiration under intracellular Ci limitation. The ∆4 phenocopy is associated with the deregulation of Ci control, an overreduced cellular state, and limited photooxidative stress. Our data suggest multiple layers of Ci regulation, including inversely regulated modules of antisense RNAs and cognate target messenger RNAs and specific trans-acting small RNAs, such as the posttranscriptional PHOTOSYNTHESIS REGULATORY RNA1 (PsrR1), which shows increased expression in ∆4 and is involved in repressing many photosynthesis genes at the posttranscriptional level. In conclusion, our insights extend the knowledge on the range of compensatory responses of Synechocystis sp. PCC 6803 to intracellular Ci limitation and may become a valuable reference for improving biofuel production in cyanobacteria, in which Ci is channeled off from central metabolism and may thus become a limiting factor.